A NEW STANDARD OF PROOF? DISCOURSES ON VISUAL DATA AFTER THE 2017 G20-PROTESTS - Venema, Rebecca; Lobinger, Katharina (AoIR Selected Papers of Internet Research, 2019)
A broad body of literature has described contemporary societies as “surveillance societies” or “surveillance cultures” and has expanded on the implications of an increasing “datafication” of society. To date, little attention has been paid to the role of visual data and their analysis in these processes. However, visual data and advancing algorithmic and facial recognition tools can provide particularly rich insights, that may imply both, important potentials and possible tensions. The contribution uses the case of controversial police investigations after the 2017 G20-summit to discuss intersections of datafication, dataveillance and visual communication and to provide insight into how different authorities and stakeholders legitimate and contest the collection of visual data and their algorithmic analysis in the political and public realm. Therefore a qualitative content and discourse analysis of news media articles, tweets, experts’ reports, police statements and minutes of parliamentary debates and committee hearings was conducted. Findings indicate that concrete practices of visual data collection and analysis remained obscure and a critical blind spot in the general media coverage. In turn, they triggered heated debates in the political realm and in specialized media coverage in which trust played a striking key role. Police authorities characterized visual data and algorithmic tools as a "new standard of proof" and thus as particularly powerful, objective and specifically trustworthy. However, indiscriminate practices of visual data collection and analysis also triggered fundamental concerns about the role and the trustworthiness of police authorities in datafied societies.